If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8a + 6 = 76 Reorder the terms: 6 + 8a = 76 Solving 6 + 8a = 76 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 8a = 76 + -6 Combine like terms: 6 + -6 = 0 0 + 8a = 76 + -6 8a = 76 + -6 Combine like terms: 76 + -6 = 70 8a = 70 Divide each side by '8'. a = 8.75 Simplifying a = 8.75
| -4x-3=-4x+4 | | x^2+50x=21279 | | (5x^2+6x+12)=0 | | Letq=180 | | a=2pir^2h | | x^2+50x=6600 | | -3x+8=-3x | | 6x+4=-2+28 | | 8y-3=3y-2+4y | | 3(4x+5)=7(x-4)+17 | | (2/3)x+(1/6)=(-5/6)x+(5/3) | | 4x+12=3(x+4) | | -56=-4x-2(-7x-2) | | 7(6+x)=6(2-x) | | 328=8(6a+5) | | -5x=-x-12 | | 10x^2-66x+72=0 | | -4x+83=-12x-125 | | 0.5y-2=-.25 | | 10+5(x-2)=4x+1 | | -29=5x-2(3x+10) | | 36x+24=10(x+2+2x) | | 7h-14=42 | | -4-3=0.4x-2y | | -4(x+4)=2(x-10) | | 5g+15=42 | | 314=-x+576 | | -4-3=0.4-2y | | 2(4x+6)=-13+1 | | 3(3z-1)-3(3-2Z)=12 | | x+1=-x+3 | | 19+2(2n-15)=1 |